Investigation of Magnetized Semiconductor and Ferrite Waveguides - Ašmontas, S.; Nickelson, L.; Mališauskas, V. (Elektronika ir Elektrotechnika, 2006)
In this paper we describe the method that allowed us to arrive at a dispersion equation for the electrodynamical analyses of open layer cylindrical gyrotropic waveguides. We numerically investigated dispersion characteristics of longitudinally magnetized semiconductor p-Ge and n-InSb waveguides at several free charge carrier concentrations N for several modes. We analyzed the n-InSb waveguide‘s dispersion dependences on the external constant magnetic field strength. We also analyzed cutoff frequency dependences of the main HE11 and the first higher mode EH11 on the N. We discovered that the waveguide wideband at the beginning decreases and then by a sudden change it increases when the concentration N is increased. We analyzed the dispersion characteristics of the longitudinally magnetized ferrite-dielectric waveguide on different electrodynamical parameters. We discovered that the working frequency band becomes wider for a microwave with a right-hand polarization when the ferrite magnetization is increased. The same dependence for a microwave with a left-hand polarization has the opposite effect. The experimental and calculated differential comparison of the phase shift of the ferrite waveguide on the value of the ferrite magnetization show that these results were in agreement with each other. Ill. 7, bibl. 12 (in Lithuanian; summaries in English, Russian and Lithuanian).